Functional Neurosurgery for Movement Disorders: Experience with Deep Brain Stimulation and Pallidotomy at a Tertiary Center in Nepal - Jha, Rajiv; Shrestha, Rajendra; Rajbhandari, Binod; Aryal, Sameer; Bhattarai, Sushil Mohan; Gautam, Sindhu; Khadka, Namrata; Jalan, Pankaj; Jha, Akschhit Raj (Nepal Journal of Neuroscience, 2026)
Background: Functional neurosurgery, particularly Deep Brain Stimulation (DBS) and ablative procedures like pallidotomy and thalamotomy, has emerged as a powerful tool in the treatment of medically refractory movement disorders. However, its application in low-resource countries like Nepal is limited. This study presents our early experience with surgical management of movement disorders at Bir Hospital using DBS and lesioning techniques. Methods: This is a prospective study from the period of April 2024 to June 2025 at the National Neurosurgical Referral Center (NNRC), National Academy of Medical Sciences (NAMS) Bir Hospital. Patients with advanced Parkinson’s disease or primary dystonia underwent surgical intervention. Four patients received bilateral Globus Pallidus internus (GPi) DBS, one patient received bilateral subthalamic nucleus(STN)DBS and three underwent unilateral radiofrequency pallidotomy. All surgeries were performed under local anesthesia except for IPG placement, which was done under general anesthesia. Patients were evaluated for improvement in tremor, rigidity, camptocormia, and dystonia. Clinical outcomes and complications were assessed over a follow-up period of up to one year. Results: All patients demonstrated significant clinical improvement in motor symptoms postoperatively. Four patients with over 1-year follow-up maintained sustained benefits. The remaining four, with early 1 month follow-up, also showed encouraging results. The outcomes between DBS and pallidotomy groups were clinically comparable. All procedures were completed safely with no perioperative complications. Cost remains the major barrier to widespread DBS adoption in Nepal. Conclusion: Both DBS and pallidotomy are effective and safe for the treatment of movement disorders. In resource-constrained settings, lesioning offers a viable and affordable alternative. Early surgical referral and government subsidy for DBS can improve access and patient outcomes in Nepal.